2019
DOI: 10.21203/rs.2.14160/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and associated factors of hepatitis B virus infection among pregnant women attending antenatal care at Agena health center, South Ethiopia, 2019: a cross sectional study

Abstract: Background; Hepatitis B virus (HBV) is the world’s most common and highly contagious liver infection. Its transmission methods are: mother to child, via open wounds, sexual contact, blood transfusion and other blood contact related activities. Prevalence of HBV among pregnant women in Africa ranges from 3.67 - 16.5% and in Ethiopia 2.4 to 8.4%. Hepatitis B infection leads to high morbidity and mortality for mother as well as for their infants due to the vertical transmission. Hence assessing the prevalence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
0
1
Order By: Relevance
“…The odds of HBV infection were about 3 times higher among pregnant mothers who had a history of hospital admission when compared to those who had no history of hospital admission. This result is in line with the study reported from Ambo town, 44 Desie, 45 Gedeo zone, 19 Agena health center, Gurage zone, 32 West Hararghe public hospitals, 46 and Egyptian. 47 This might be due to that the hospitalized women might easily acquire the infection during a different procedure than the pregnant women who had no history of hospital admission.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The odds of HBV infection were about 3 times higher among pregnant mothers who had a history of hospital admission when compared to those who had no history of hospital admission. This result is in line with the study reported from Ambo town, 44 Desie, 45 Gedeo zone, 19 Agena health center, Gurage zone, 32 West Hararghe public hospitals, 46 and Egyptian. 47 This might be due to that the hospitalized women might easily acquire the infection during a different procedure than the pregnant women who had no history of hospital admission.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of HBV infection was nearly similar to results reported in Shone, Nekemte, Bishoftu, and Felegehiwot referral hospitals 4.9%, 27 5.8%, 28 6.5%, 18 and 4.7% 29 , respectively. The result of this study was relatively high when compared to the result reported from Addis Ababa at 3.7%, 20 7.8% Southern Ethiopia, 30 Gandhi memorial hospital at 2.3%, 31 Agena health center in the Gurage zone at 4.1%, 32 Uganda at 2.1% 33 , and Rwanda 3.1%. 34 The variation might be due to the differences in cultural practices and strategies used for infection prevention and risky behavior practices.…”
Section: Discussioncontrasting
confidence: 55%